L’enseignement supérieur aux Émirats Arabes Unis, entre émiratisation et contraintes du marché - William Gueraiche (Revue des Mondes Musulmans et de la Méditerranée)
Since the founding of the first public university in 1977, the federal government of the UAE has used higher education as its primary means to achieve the emiratization (nationalization of the civil service and the business sector). The growth of private universities that started in the mid 1990s’ has not changed this objective, but the ministry of higher education and scientific research has become a regulatory body whose mission is to manage the higher education market through accreditation processes. In parallel, there was a fierce competition between four emirates (Abu Dhabi, Dubai, Sharjah and Ras al Khaimah) to become the university hub of the UAE -- and the rest of the Gulf. To fuel their ambitions these emirates attempt to create partnerships with prestigious international universities. The competition has turned out to Abu Dhabi's advantage: the emirate could well become the education capital of the UAE, perhaps of the rest of the region, and has led to a new balance of power between the federal and local governments.